Analisis Ekonomi Sumber-Sumber Pendapatan Asli Daerah (PAD) Kabupaten Ngada Tahun 2018-2022 - Dopo, Duns Skoius Klementinus; Sagajoka, Estherlina; Sedho, Yuliana (JURNAL EQUILIBRIUM, 2023)
This study aims to analyze (1) the level of contribution of each type of regional tax, regional levies, results of separated regional wealth management and other legitimate PAD of Ngada Regency in 2018-2022. (2) the level of effectiveness of each type of regional tax, regional levies, results of separated regional wealth management and other legal PAD against regional original income (PAD) of Ngada Regency in 2018-2022. This study uses a qualitative descriptive analysis method. The data used is financial data from BAPENDA of Ngada Regency in the form of targets and realization of local taxes, regional levies, results of separated regional wealth management and other legal PAD for 2018-2022. The results of this study are: (1) of the four sources of original regional income, only other legitimate PAD contribute very well, while the 3 sources of original regional income have not contributed to regional original income (2) the level of effectiveness 8 local taxes, namely restaurant tax, PJU tax, hotel tax, entertainment tax, advertisement tax, MBLB tax, PBB-P2 and BPHTB. For 5 years 3 local taxes the average effectiveness exceeds 100% with very effective criteria. (3) the level of effectiveness of regional levies is still below 100%. (4) the level of effectiveness of regional wealth management results has been very effective. (5) the level of effectiveness of other legitimate PAD is still below 100%.